Review of the millipede family Diplomaragnidae of Japan, with description of a new species and the restoration of the combination Diplomaragna hokkaidensis (Verhoeff, 1939) (Diplopoda, Chordeumatida, Diplomaragnidae) - Mikhaljova, Elena V.; Korsós, Zoltán (Zootaxa, 2015)
Diplomaragnidae are currently represented in Japan by ten species in three genera. One species is described here as new to science: Tokyosoma flexuosum sp. n. Maritimosoma hokkaidense (Verhoeff, 1939) is returned to Diplomaragna: Diplomaragna hokkaidensis (Verhoeff, 1939). The distributions of the Japanese species of Diplomaragnidae are mapped.